Functional chains of knowledge management: effects on firms' innovative performance - Uwe Cantner; Kristin Joel (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
The aim of this paper is to investigate the role of Knowledge Management (KM) for the innovation success of firms. It is assumed that the functional chains of KM lead directly and indirectly to more innovative success via enhancing the recombination of internal and external knowledge assets. To analyse the embedding of KM in a firms internal system of innovation we establish a structural equation model. We capture KM as latent concept and trace different functional chains by which KM impacts. Using data on KM and innovation success of 351 German firms of the manufacturing sector and knowledge-intensive services located in Thuringia and Hesse, our findings confirm the (dynamic) capability function of KM, which leads via improving exploitation of internal and external innovation assets to more innovation success.
Keywords: O32; D21; C3; 330; Knowledge management; innovation; absorptive capacity; resource-based view; structural equation modelling; Wissensmanagement; Innovation; Industrielle Forschung; Erfolgsfaktor; Deutschland